Traditional Foods General and Consumer Aspects - Kristbergsson, Kristberg; Oliveira, Jorge; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2016)
This first volume of the Trilogy of Traditional Foods, part of the ISEKI Food Series, covers general and consumer aspects of traditional foods. It offers numerous recipes of traditional foods from across the world, with some chapters providing detailed descriptions on how to mix, cook, bake or store a particular food item in order to produce the desired effect. Traditional Foods; General and Consumer Aspects is divided into six sections. The first section focuses on general aspects of traditional foods and covers the perception of traditional foods and some general descriptions of traditional foods in different countries. This is followed by sections on Traditional Dairy Products, Traditional Cereal Based Products, Traditional Meat and Fish Products, Traditional Beverages and Traditional Deserts, Side Dishes and Oil products from various countries. The international List of Contributors, which includes authors from China, Bulgaria, Portugal, France, Norway, Romania, Slovakia, and Brazil, to name a few, shows its truly international perspective. The volume caters to the practicing food professional as well as the interested reader.
European Consumers' Definition and Perception of Traditional Foods -- Consumers' Valuation and Quality Perception of Kid's Meat From Traditional "Cabrito Da Gralheira" - Protected Geographical Indication -- Traditional Fermented Foods in Thailand -- Increasing Romanian's Traditional Food Added Value through Integration into the Protected Geographical Designations System -- Traditional Foods in Slovakia -- Traditional Foods in Turkey: General and Consumer Aspects -- Indian Traditional Fermented Dairy Products -- Traditional Bulgarian Dairy Food -- Dulce de Leche: Technology, Quality and Consumer Aspects of the Traditional Milk Caramel of South America -- Austrian Dumplings -- French Bread Baking -- Traditional Rye Sourdough Bread in the Baltic Region -- The Legume Grains: When Tradition Goes Hand In Hand with Nutrition -- Traditional Food Products from Prosopis sp. Flour -- Amaranth: an Andean Crop with History. It´s feeding reassessment in America -- Yunnan Fermented Meat: Xuanwei Ham, Huotui -- Selected Viennese Meat Specialties -- Norse Dried Fish -- Utilization of Different Raw Materials from Sheep and Lamb in Norway -- Muxama and Estupeta: Traditional Food Products Obtained from Tuna Loins in South Portugal and Spain -- Salting and Drying of Cod -- Brazilian Charqui Meats -- German Beer -- "Pálinka" - Hungarian Distilled Fruit -- Tokaji Aszú - "the Wine of Kings, the King of Wines" -- Mead - The Oldest Alcoholic Beverage -- Midus - a Traditional Lithuanian Mead -- Horchata -- "Dobos": A super-cake from Hungary -- Traditional Green Table Olives from the South of Portugal -- Extra Virgin Olive Oil and Table Olives from Slovenian Istra -- A Perspective on Production and Quality of Argentinian Nut Oils -- Pupunha (Bactris gasipaes): General and Consumption Aspects.
Keywords: Food science; Food -- Microbiology; Nutrition .; Food Science; Food Microbiology; Nutrition